Oil Content and Fatty Acid Compositions of Some Oil Sources - Musa Özcan, Mehmet; Endes, Züleyha; Al-Juhaimi, Fahad (Asian Journal of Chemistry, 2012)
The oil yields of seed used in this study ranged between 27.1 to 39.8 % of the dry weight. Results showed that the oils of safflower 1 seeds used in this study had higher linoleic acid content (78.06 %) than those of other linoleic acid contents. On the other hand, oleic acid contents of seed oils varied between 14.21 % (safflower 1) to 67.79 % (rape 2). Results showed that the oils of canola 4, rape 1, rape 2, canola 3 and canola 5 oils had higher oleic acid (61.40-67.79 %). As a result, the present study showed that the seeds are to be a potential source of valuable oil which might be used for edible and other industrial applications.